2012
DOI: 10.3390/min2020085
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Change at the Setting-up of the Crossed-Lamellar Layer in Nerita undata Shell (Mollusca, Gastropoda)

Abstract: Nerita undata is a marine gastropod, the shell of which consists of an external layer composed of very fine, long and undulating calcite prisms, and of an internal aragonite crossed-lamellar layer. As for any Ca-carbonate shell, both layers are composite materials, resulting from the sub-micrometric association of organic macromolecules with the mineral phase. But at the transition between the two layers, in situ synchrotron-based mapping using µ-XANES spectroscopy performed at the S K-edge and SR-FTIR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Electron microprobe analyses have previously shown that the shells of some Haliotis species comprise aragonite and calcite that are irregularly dispersed and mixed (Dauphin et al, 2007). In regularly layered mollusk shells, a detailed examination of the boundary between the main layers shows transitional stages in both composition and structure (Dauphin et al, 2008, 2012; Farre et al, 2011; Nouet et al, 2012). In such shells, the main layers are easy to separate for various analyses, whereas the structure and composition of the transition layer is only known using in situ analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microprobe analyses have previously shown that the shells of some Haliotis species comprise aragonite and calcite that are irregularly dispersed and mixed (Dauphin et al, 2007). In regularly layered mollusk shells, a detailed examination of the boundary between the main layers shows transitional stages in both composition and structure (Dauphin et al, 2008, 2012; Farre et al, 2011; Nouet et al, 2012). In such shells, the main layers are easy to separate for various analyses, whereas the structure and composition of the transition layer is only known using in situ analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microprobe analyses have previously shown that the shells of some Haliotis species comprise aragonite and calcite that are irregularly dispersed and mixed~Dauphin Farre et al, 2011;Nouet et al, 2012!. In such shells, the main layers are easy to separate for various analyses, whereas the structure and composition of the transition layer is only known using in situ analyses. The efficiency of such techniques allows us to improve our knowledge of the complex and irregular shell of abalone.…”
Section: Discussionmentioning
confidence: 99%
“…S3). Crossed-lamellar microstructure is the most common microstructure in mollusks (Salinas and Kisailus 2013; Voltzow 1994), but has a high degree of order (Salinas and Kisailus 2013), requiring a complex interaction with organic macromolecules (Weiner et al 1984; de Paula and Silveira 2009; Nouet et al 2012; Hickman 2013). In both turritellids and other taxa, septa form in clear continuity with the inner shell layer, with lamellae continuous in orientation where they intersect the inner shell layer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Septa, like the majority of calcium carbonate structures in gastropods, have been presumed to be constructed by mantle tissue in direct contact with the location where new shell material is being laid down (Andrews 1971; Kohn et al 1979; Bandel 1990, 1991; de Paula and Silveira 2009; Nouet et al 2012). Fine study of the microstructure of Charonia variegata indicates that septa are initially spherulitic prismatic and grade into crossed-lamellar structure, “presumably with increased mantle control” (Bandel 1979, 1990; Hickman 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In shells of the gastropod Nerita undata Linnaeus 1758, the structural and mineralogical shifts from the outer calcitic layer towards the inner aragonitic crossed lamellar layer are also complex (Nouet et al. ).…”
Section: Discussionmentioning
confidence: 99%